Analisis Pelaksanaan Pembelajaran Tatap Muka (PTM) pada Masa New Normal di SDN Karawaci 13 - Morningrum, Roro Dewila; Sari, Mayang; Magdalena, Ina; Hasanah, Paujatul; Prastio, Feby Dwi (Lembaga Yasin AlSys, 2022)
The Covid-19 virus pandemic in Indonesia has had a significant impact on several sectors such as the economy, industry, education and so on. In this article, we explain the impact of student habits while studying online (online) for a long time, namely for 2 years, the Covid-19 virus is very influential in the world of children's education. In this article, we explain how student activities before and after the Covid-19 outbreak, the good and bad impacts of each learning for students, as for changes in the mechanism in learning. This article was made using a qualitative method, the data was taken through interviews with grade 1 teachers at the Karawaci 13 elementary school. Based on field observations, interviews, tests, and field notes, information was obtained that the implementation of limited PTM at SD Negeri Karawaci 13 was carried out according to the PTM implementation guidelines during the pandemic with an emphasis on implementing strict health protocols. After the vaccination program which caused the spread of COVID-19 to decrease, the government issued a policy to conduct a face-to-face learning process (offline) so as to require students to start returning to school and carry out activities according to the activities at their school.